The Baltimore City Code, Containing the Public Local Laws of Maryland Relating to the City of Baltimore, and the Ordinances of the Mayor and City Council, in Force on the First Day of November, 1891, with a Supplement, Containing the Public Local Laws Relating to the City of Baltimore, Passed at the Session of 1892 of the General Assembly, and also the Ordinances of the Mayor and City Council, Passed at the Session of 1891-1892, and of 1892-1893, up to the Summer Recess of 1893 at 589, City Code, (1879,) Art. 20, sec. 53 § 63 - (:unkn) unknown (General Publisher, 1879)
All gunpowder brought within the limits of the city by land, or into the port or harbor, in any ship or vessel, other than a ship or vessel of war, shall be stored in the said magazine as aforesaid; if brought by land as aforesaid, within seventeen hours thereafter; if brought into the port or harbor as aforesaid, within forty-eight hours after the ship or other vessel thus bringing it shall have broken bulk; proved the quantity thus brought in shall exceed the weight of one quarter barrel as above defined
--
Keywords: GUN POWDER TRANSPORTATION